2006
DOI: 10.1002/bit.21230
|View full text |Cite
|
Sign up to set email alerts
|

Improved catalytic properties of immobilized lipases by the presence of very low concentrations of detergents in the reaction medium

Abstract: The addition of a very small concentration of a detergent (in many instances under the critical micellar concentration (cmc)) has been found to greatly increase the activity of immobilized lipases, using those from Pseudomonas fluorescens (PFL) and Candida antarctica (isoform B) as model enzymes. However, the detergents may also have a negative effect on enzyme activity; in fact, for all enzyme preparations and substrates the activity/detergent concentration curve reached a maximum value and started to decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 70 publications
2
43
0
1
Order By: Relevance
“…As previously reported [15], we observed a 5-fold increase on the specific activity of the partially purified soluble lipase in presence of 0.1% Triton X-100, probably due to the disruption of protein aggregates and/or to the shift on the closed/open equilibrium towards the open form of the lipase [16].…”
Section: Immobilization In the Presence Of Triton X-100supporting
confidence: 69%
See 1 more Smart Citation
“…As previously reported [15], we observed a 5-fold increase on the specific activity of the partially purified soluble lipase in presence of 0.1% Triton X-100, probably due to the disruption of protein aggregates and/or to the shift on the closed/open equilibrium towards the open form of the lipase [16].…”
Section: Immobilization In the Presence Of Triton X-100supporting
confidence: 69%
“…Recently, it has been shown that lipase activity in aqueous and anhydrous media can be improved in the presence of detergents [14][15][16][17] probably due to the breakage of lipase aggregates and/or to the shift on the closed-open equilibrium of the individual lipase molecules [16]. In immobilized lipases, the detergent Triton X-100 is commonly used to desorb the enzyme from the support, but in some instances it has been added during the immobilization procedure resulting in good immobilization yields (60-100%) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme activity increment could be related to the stabilization of the lipase open form stimulated by detergent molecule interaction with the hydrophobic catalytic groove as in the BTL2 open form with TRT1 and TRT2; this is a known effect in soluble and immobilized lipases (32). BTL2 activity decrease may be related to the inhibitory effect of Triton X-100 at concentrations higher than 1 mM in which a competitive inhibitory effect could prevent the substrate catalysis, as was also observed in other lipases (33).…”
Section: Resultsmentioning
confidence: 76%
“…The Triton X-100, by being a surfactant, has both hydrophilic (head) and hydrophobic (tail) fractions, and when in contact with lipase it is open arranged, exposing its active site. According to Fernandez-Lorente et al (2007), the hydrophobic portion of Triton binds to the active site of lipase and may cause a distortion of the enzyme or inhibition of its catalytic activity (competitive inhibition), a competition between Triton and substrate, hindering the access of substrate to the active site of lipase and limiting the product formation. Nevertheless, this behavior depends on the type of support used to prepare the immobilized system, as described by Cabrera et al (2009).…”
Section: Glycerolysis Reactions In Batch Reactormentioning
confidence: 99%